Talent identification and development in soccer - Williams, A. M.; Reilly, T. (Journal of Sports Sciences, 2000)
In this review, we attempt to integrate the main research findings concerned with talent identification and development in soccer. Research approaches in anthropometry, physiology, psychology and sociology are considered and, where possible, integrated. Although some progress has been made in identifying correlates of playing success, it appears that no unique characteristics can be isolated with confidence. Both biological and behavioural scientists have indicated a strong genetic component in performance of sports such as soccer; nevertheless, the influence of systematic training and development programmes should not be underestimated. Weconclude that the sport and exercise sciences have an important support role in the processes of identifying, monitoring and nurturing talented soccer players towards realizing their potential.